Trade patterns and economic evolution - T. R. G. Bingham (Intereconomics, 1974)
Finland is the last one of the non-applicant EFTA countries to conclude a free trade agreement with the EC. The author takes a favourable view of its prospects particularly since it has come into force just as a cyclical down-turn was getting under way.
Keywords: 330; Finland